HEDGING THROUGH THE USE OF MODAL AUXILIARIES IN ENGLISH ACADEMIC DISCOURSE - Tofan Dwi Hardjanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
As a communicative strategy, hedging plays a central role in academic writing. Numerous different linguistic forms can be used to express this strategy. This article attempts to investigate modal auxiliary verbs as the principal means of expressing hedging in English academic discourse. For this purpose, a corpus of 75 primary empirical research articles from economics, linguistics, medicine, natural sciences and engineering was analyzed quantitatively with the help of corpus linguistic method. The results revealed that modal auxiliaries were used most frequently in linguistics and economics and least frequently in engineering and natural sciences while their use in medicine came in between. This seems to suggest that there is noticeable disciplinary variation in the degree of hedging through the use of modal auxiliaries in English research articles. Modal auxiliaries tend to be more common in soft sciences than in hard sciences whereas their use in health sciences in comparison with soft and hard sciences does not seem to show any significant difference.